Peningkatan Kemampuan Siswa Menulis Bahasa Inggris dengan Metode Problem Based Learning pada kelas X SMKN 1 Tapaktuan - Yulita Halim (Indo Publishing, 2026)
This Classroom Action Research (CAR) aims to improve the English writing skills of Grade X students at SMKN 1 Tapaktuan through the implementation of the Problem-Based Learning (PBL) model. The study was motivated by the students' low writing proficiency and high levels of writing anxiety, stemming from the dominance of conventional, teacher-centered instructional methods. The research was conducted over two cycles using the Kemmis and McTaggart spiral model, comprising the stages of planning, action implementation, observation, and reflection. The subjects of the study were Grade X students at SMKN 1 Tapaktuan. Data were collected using a triangulation technique that combined quantitative data—specifically, writing performance tests (post-tests) administered at the end of each cycle—with qualitative data derived from activity observation sheets and field notes. The findings indicate that the implementation of the Problem-Based Learning (PBL) method is empirically effective in enhancing students' English writing abilities, improving both the quality of written output and the level of engagement in the learning process among Grade X students at SMKN 1 Tapaktuan.